ANALISIS KIM DALAM MEWUJUDKAN INFORMASI PUBLIK DI DESA SIDOMULYO KECAMATAN ANGGANA KUKAR - Hairunnisa Hairunnisa; Muhammad Noor (Jurnal Riset Komunikasi (JURKOM), 2018)
The purpose of the study was to describe, and to analyze the Community Information Group in Achieving Public Information in Sidomulyo Village, Anggana, Kutai Kartanegara. Data collection was done by Snowball Sampling method by determining Key Informant using purposive sampling method toward respondent in Sidomulyo Village. Primary data obtained from direct interviews with respondents based on interview guidelines, while secondary data obtained from the book. The results showed that in the absorption of community aspirations and information distribution by KIM is still running well However, there are weaknesses in human resources in internal KIM members busy each - each with a profession so that the performance of KIM less than the maximum. The Community Information Group (KIM) to accommodate the aspirations is already running but does not increase significantly. The form of application in the dissemination of information through blogs, Websites, and Social Media. This is good only to improve communication between the village apparatus and the Kutai Kartanegara Regional Government. The role of coach is expected by KIM Sidomulyo Village because for facilities and services if it can be fulfilled by village apparatus.